Beng prende Portugues Malaká (Papiá Cristang) = Come, let's learn Portugues Malaká (Papiá Cristang) - Singho, Michael Gerard; Maria, Sara Ferederica Santa; Pinto, Dolores; Pillai, Stefanie; Kajita, Angela; Philip, Adriana (University of Malaya Press, 2016)
Do you occasionally speak Portugues Malaká (Papiá Cristang). Have you ever found yourself writing a text message in Portugues Malaká (Papiá Cristang) and stopped to wonder how to spell a certain word you always use? Or are you a beginner, curious about this unique language? Whether you are already familiar with it or a beginner starting from scratch, this book will guide you through the spelling, pronunciation and use of Portugues Malaká (Papiá Cristang). You can choose to follow the lessons one by one, or to go straight to your topic of interest; the activities can be done at your own pace, and do not require you to be in a classroom or have a strict schedule. So what are you waiting for? Beng prende Portugues Malaká (Papiá Cristang)!